Borosiloxane modified phenolic resin flame retardant, transparent flame retardant polycarbonate composite material and preparation method thereof

Through the development of borosiloxane-modified phenolic resin flame retardant, the shortcomings of polycarbonate materials in flame retardant performance, transparency and physical properties have been solved, and the comprehensive improvement of high thermal stability, good flame retardant effect and good mechanical properties have been achieved.

CN116333240BActive Publication Date: 2025-03-25SHANGHAI KUMHO SUNNY PLASTICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310137366.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-03-25
Estimated Expiration
2043-02-20

AI Technical Summary

Technical Problem

The existing polycarbonate (PC) materials have shortcomings in flame retardant properties, transparency and physical properties, and cannot meet the actual needs of industries such as electronics and electrical appliances and construction materials.

Method used

A borosiloxane modified phenolic resin flame retardant is developed, and the flame retardant with high thermal stability and good flame retardant effect is prepared by stirring and mixing boric acid, oligosiloxane polymer and phenolic resin in a specific proportion, and prepared by heating, stirring and distillation.

Benefits of technology

It realizes the stable flame retardant effect of polycarbonate materials at a thickness of 1.6mm, while maintaining good mechanical properties and light transmittance, meeting the needs of high flame retardant properties and transparent materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004086382130000031
    Figure BDA0004086382130000031
  • Figure BDA0004086382130000061
    Figure BDA0004086382130000061
  • Figure BDA0004086382130000071
    Figure BDA0004086382130000071
Patent Text Reader

Abstract

The present invention relates to a borosiloxane modified phenolic resin flame retardant, a transparent flame retardant polycarbonate composite material and a preparation method thereof. The flame retardant comprises the following components by weight: 1-5 parts of a boron compound; 5-20 parts of an oligosiloxane polymer; and 5-20 parts of a phenolic resin. The transparent flame retardant polycarbonate composite material comprises the following components by weight: 70-98 parts of a polycarbonate resin; and 1-20 parts of a borosiloxane modified phenolic resin flame retardant. The polycarbonate resin has a melting point of 220-230°C and a density of 1.18-1.22 kg / cm 3 The particle size of the borosiloxane modified phenolic resin flame retardant is 50-500 mesh, and the above raw materials are blended and granulated to obtain a transparent polycarbonate composite material with a 1.6mm vertical combustion V-0 flame retardant grade. Compared with the prior art, the synthesis process of the present invention is simple and conducive to large-scale application, and can give the polycarbonate a stable flame retardant effect with a thickness of 1.6mm, while having good mechanical properties and light transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer material modification, and in particular to a borosiloxane-modified phenolic resin flame retardant, a transparent flame-retardant polycarbonate composite material and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is an engineering plastic with excellent performance. It has certain flame retardant properties. The limiting oxygen index can reach 26% and the vertical combustion grade is V-2. However, in many industries, such as electronic appliances, construction materials, etc., the flame retardant properties of PC still cannot meet the requirements of practical applications. Commonly used flame retardants for PC include inorganic flame retardants, sulfonate flame retardants, silicone flame retardants, phosphorus flame retardants, phosphazene flame retardants, and halogen flame retardants.

[0003] Inorganic flame retardants tend to aggregate during processing, and if added in large quantities, the material cannot be made transparent. Sulfonate and silicone flame retardants are added in low quantities, but the flame retardant effect is unstable. Phosphorus and phosphazene flame retardants will greatly affect some of the physical properties of PC, such as impact strength and heat deformation temperature. Halogenated flame retardants produce a large amount of toxic and harmful gases after combustion, which pollute the environment.

[0004] Phenolic resin has a high carbonization rate, but poor thermal stability, and a decomposition temperature between 220-250°C, which is lower than the general processing temperature of PC. Therefore, it is not possible to directly use phenolic resin as a flame retardant for PC to improve its flame retardant properties. Therefore, finding a suitable flame retardant to meet the market demand for flame retardancy and transparency of PC while maintaining certain physical properties has become a research hotspot. Summary of the invention

[0005] The purpose of the present invention is to overcome at least one of the defects of the above-mentioned prior art and to provide a borosiloxane-modified phenolic resin flame retardant, a transparent flame retardant polycarbonate composite material and a preparation method thereof, which has a simple synthesis process and is conducive to large-scale application, can give polycarbonate with a stable flame retardant effect of 1.6 mm thickness, and has good mechanical properties and transmittance.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The inventors learned that phenolic resin has a very high residual carbon rate and is often used as a refractory material. However, its decomposition temperature is only about 220°C, which is lower than the processing temperature of PC. The decomposition of phenolic resin mainly starts from the phenolic hydroxyl group. The heat resistance of phenolic resin can be improved by boron modification to convert the phenolic hydroxyl group into a boron oxygen structure. The introduction of siloxane can reduce the initial viscosity when boron reacts with phenolic resin, which is conducive to the complete reaction of boric acid. In addition, siloxane itself has a certain flame retardant effect. Therefore, the development of a boron-containing siloxane-modified phenolic resin flame retardant can provide a possible solution to the above-mentioned flame retardant defects, and the following specific solutions are proposed:

[0008] A borosiloxane-modified phenolic resin flame retardant, comprising the following components in parts by weight:

[0009] 1-5 parts of boron compound, preferably 1-2 parts;

[0010] 5-20 parts of oligosiloxane polymer;

[0011] 5-20 parts of phenolic resin.

[0012] Furthermore, the boron compound includes boric acid, boric acid esters or borate salts, specifically including one or more of boric acid, trimethyl borate, triethyl borate, triphenylborate, potassium tetraphenylborate or sodium tetraphenylborate;

[0013] The oligosiloxane polymer is a polymer having an alkyl or phenyl group in the branched chain and terminated with a hydroxyl group, a phenol group or an alkoxy group, including one or more of polydimethylsiloxane, polymethylphenylsiloxane, polymethylethoxysiloxane, polymethylvinylsiloxane, polymethylchlorophenylsiloxane, polymethyltrifluoropropylsiloxane, polymethylhydroxysiloxane, polymethylhydrogensiloxane, polyethylhydrogensiloxane or polyhydroxyhydrogensiloxane terminated with a hydroxyl group or an alkoxy group.

[0014] Preferably, the oligosiloxane polymer is liquid at 25°C and has a density of 1.01-1.15 g / cm 3 , the side chains are methyl and phenyl, and are terminated with alkoxy groups.

[0015] Furthermore, the phenolic resin is in liquid or powder form, wherein the viscosity of the liquid phenolic resin is between 2000-20000 Pa·s at 20°C, and the softening point of the powdered phenolic resin is between 85-115°C.

[0016] Preferably, the viscosity of the liquid phenolic resin is between 2000-10000 Pa·s, and the softening point of the powdered phenolic resin is between 95-105°C.

[0017] A method for preparing the borosiloxane-modified phenolic resin flame retardant as described above, the method comprising the following steps:

[0018] Stirring and mixing the components according to weight to obtain a mixed material;

[0019] The mixed material is heated, stirred and distilled through a reactor;

[0020] Then pour it into anhydrous ethanol and dissolve it completely, then pour it into water to precipitate;

[0021] The precipitated product is filtered and dried, and then crushed and sieved to obtain a borosiloxane-modified phenolic resin flame retardant.

[0022] Furthermore, the heating process is: from room temperature to 140-250°C, the heating rate is 10-30°C / min; the stirring rate is 180-200 rpm; the drying temperature is 60-80°C, and the screen is 50-500 mesh.

[0023] A transparent flame-retardant polycarbonate composite material, comprising the following components in parts by weight:

[0024] Polycarbonate resin 70-98 parts;

[0025] 1-20 parts of the borosiloxane modified phenolic resin flame retardant as described above.

[0026] Furthermore, the polycarbonate resin has a melting point of 220-230°C and a density of 1.18-1.22 kg / cm 3 The particle size of the borosiloxane modified phenolic resin flame retardant is 50-500 mesh, preferably 100-400 mesh, and more preferably 300-400 mesh.

[0027] Furthermore, the composite material further comprises the following components in parts by weight:

[0028]

[0029] The sulfonate flame retardant includes one or a mixture of potassium benzenesulfonylbenzenesulfonate (KSS), lithium perfluorobutylsulfonate (LiFBS), sodium perfluorobutylsulfonate (NaFBS), potassium perfluorobutylsulfonate (KFBS), cesium perfluorobutylsulfonate (CsFBS), potassium perfluorooctanesulfonate (KFOS), potassium perfluoromethanesulfonate (KFMS), potassium p-toluenesulfonate (KTS) or sodium trichlorophenylsulfonate (STB);

[0030] The compatibilizer includes acrylonitrile-styrene copolymer grafted with maleic anhydride or acrylonitrile-styrene copolymer grafted with glycidyl methacrylate;

[0031] The antioxidant includes one or a mixture of aromatic amine antioxidants, hindered phenol antioxidants, phosphite antioxidants, thioester antioxidants, aromatic phosphates or pentaerythritol esters;

[0032] The lubricant includes one or more of silicone oil, white mineral oil, fatty acid amide, barium stearate, magnesium stearate, paraffin, polyethylene wax, ethylene bis stearic acid amide, ethylene-vinyl acetate copolymer, pentaerythritol stearate, ethylene-acrylic acid copolymer or aromatic phosphate. The lubricant includes one or more of silane polymer, solid paraffin, liquid paraffin, fatty acid salt, calcium stearate fatty acid amide, calcium stearate, zinc stearate, stearic acid amide, methylene bis stearic acid amide, N,N-ethylene bis stearic acid amide.

[0033] A method for preparing the transparent flame-retardant polycarbonate composite material as described above, the method comprising the following steps:

[0034] The components are fully mixed by weight to obtain a mixed material; the mixing time is 5-30 minutes;

[0035] The mixed material is placed in a twin-screw extruder, and after melt extrusion and granulation, a flame-retardant transparent polycarbonate composite material is obtained. The screw speed is 180-600rpm;

[0036] Furthermore, the feeding port temperature of the twin-screw extruder is 50-60°C, including 10 temperature control zones, the temperature of temperature control zone 1-2 is 180-280°C, the temperature of temperature control zone 3-4 is 200-280°C, the temperature of temperature control zone 5-6 is 220-280°C, the temperature of temperature control zone 7-8 is 220-280°C, and the temperature of temperature control zone 9-10 is 240-280°C.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) In the present invention, the production process of the borosiloxane-modified phenolic resin flame retardant is simple, which is conducive to large-scale industrial production. The flame retardant does not require an additional catalyst, does not require a solvent during the reaction process, and the addition of siloxane allows the viscosity of the system to be effectively controlled during the synthesis process;

[0039] (2) In the present invention, the phenolic resin modified by boric acid and siloxane has higher thermal stability and residual carbon rate, which means better flame retardant effect. Moreover, due to its high temperature resistance, it can support the subsequent composite material processing process. At the same time, the refractive index of phenolic resin is similar to that of polycarbonate, which is beneficial to the improvement of product transmittance. DETAILED DESCRIPTION

[0040] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0041] A borosiloxane-modified phenolic resin flame retardant and a preparation method thereof, comprising the following steps:

[0042] a. Prepare materials according to components and weight;

[0043] b. Stirring and mixing the components under constant temperature and ultrasonic conditions to obtain a mixed material;

[0044] c. The mixture obtained in step b is heated, stirred, and dehydrated by distillation in a reactor.

[0045] d. Pour into anhydrous ethanol and dissolve completely, then pour into deionized water to precipitate

[0046] e. The precipitated product is filtered, dried, crushed and sieved to obtain the product.

[0047] A transparent flame-retardant polycarbonate composite material and a preparation method thereof, comprising the following steps:

[0048] a. Prepare materials according to components and weight;

[0049] b. Stirring and mixing the components under constant temperature and ultrasonic conditions to obtain a mixed material;

[0050] c. The mixture obtained in step b is heated, stirred, and dehydrated by distillation in a reactor.

[0051] d. Pour into anhydrous ethanol and dissolve completely, then pour into deionized water to precipitate

[0052] e. The precipitated product is filtered, dried, crushed and sieved to obtain the product.

[0053] In the following examples, the flame retardant properties are tested according to the UL-94 standard; the light transmittance is tested according to ASTM D1003; the tensile properties are tested according to ASTM D638 (tensile rate is 50 mm / min); the bending properties are tested according to ASTM D790 (bending rate is 1.25 mm / min); the Izod notched impact properties are tested according to ASTM D256; and the melt flow rate is tested according to ASTM D1238 (300°C×1.2 kg).

[0054] Each component of the embodiments and comparative examples is selected from the following raw materials:

[0055] Polycarbonate uses Mitsubishi Gas's S-2000F

[0056] Boron compounds are selected from Aladdin's analytical grade boric acid

[0057] The siloxane used is SFR320 from Momentive

[0058] The phenolic resin uses Henan Borun's 6823 resin powder

[0059] Sulfonate flame retardant selected from Shanghai Huiyan's HY-2025

[0060] The antioxidant used is Irganox 168 from Ciba

[0061] The lubricant is P0739 from Shanghai TCI

[0062] Examples 1-6

[0063] A borosiloxane-modified phenolic resin flame retardant, a transparent flame-retardant polycarbonate composite material and a preparation method thereof, as follows:

[0064] (1) Preparation of borosiloxane modified phenolic resin flame retardant

[0065] In a nitrogen atmosphere, 5 parts of phenolic resin powder, 5 parts of siloxane and 1 part of boric acid were added to a reactor and placed in a heating jacket for heating and stirring. The heating temperature was set to 200°C, the heating rate was 10°C / min, the stirring rate was 180 rpm, and water was distilled off at the same time. After the reaction for 30 minutes, the product was placed in anhydrous ethanol and dissolved completely, and then a large amount of deionized water was poured to precipitate the product. The precipitated product was filtered and dried in an oven at 80°C for 24 hours to obtain the product BSiPR. Six types of BSiPR as shown in Table 1 were obtained through sieves of different particle sizes.

[0066] Table 1 Screen mesh number and flame retardant code

[0067] Mesh 50 100 200 300 400 500 Code BSiPR0 BSiPR1 BSiPR2 BSiPR3 BSiPR4 BSiPR5

[0068] (2) Preparation of polycarbonate composite materials containing borosiloxane-modified phenolic resin flame retardant

[0069] The components and contents are shown in Table 2:

[0070] Table 2 Components and contents

[0071]

[0072] The preparation method is as follows:

[0073] a. Prepare materials according to components and weight;

[0074] b. Place the components in a mixer and mix for 20 minutes to obtain a mixed material;

[0075] c. The mixed material obtained in step b is passed through the main feeding device, the screw speed is controlled to be 600 rpm, and the product is obtained through melt extrusion and granulation.

[0076] The twin-screw extruder includes 10 temperature control zones, the temperature of temperature control zone 1-2 is 200°C, the temperature of temperature control zone 3-4 is 230°C, the temperature of temperature control zone 5-6 is 240°C, the temperature of temperature control zone 7-8 is 250°C, and the temperature of temperature control zone 9-10 is 250°C. The main feeding device is located in the first zone, and the side feeding device is located in the sixth zone.

[0077] Comparative Example 1

[0078] In Comparative Example 1, the preparation method is the same as that of Examples 1-6, wherein the components and contents are shown in Table 2.

[0079] The particles prepared in the above Examples 1-6 and Comparative Example 1 were tested, and the results are shown in Table 3.

[0080] Table 3 Test results of products of Examples 1-6 and Comparative Example 1

[0081]

[0082] As shown in Table 3, the UL94 flame retardant grade of the sample with 100-400 mesh borosiloxane modified phenolic resin flame retardant is V-0, and the tensile strength, bending strength and notched impact strength have little change while having higher flame retardant performance. The transparency is slightly reduced but can still meet the application requirements in the field of transparent flame retardant. The particles of the 50 mesh sample are large, and the 500 mesh sample is easy to agglomerate during processing, resulting in a decrease in the notched impact strength and flame retardant performance of the material.

[0083] Embodiment 7-11

[0084] The components and contents are shown in Table 4:

[0085] Table 4 Components and contents

[0086]

[0087] The preparation method is as follows:

[0088] a. Prepare materials according to components and weight;

[0089] b. Place the material in a mixer and mix for 20 minutes to obtain a mixed material;

[0090] c. The mixed material obtained in step b is fed into a twin-screw extruder through a main feeding device, and the glass fiber is fed into a side feeding device. The screw speed is controlled to be 180-600 rpm. The product is obtained by melt extrusion and granulation.

[0091] The twin-screw extruder includes 10 temperature control zones, the temperature of temperature control zone 1-2 is 140-240°C, the temperature of temperature control zone 3-4 is 200-240°C, the temperature of temperature control zone 5-6 is 200-240°C, the temperature of temperature control zone 7-8 is 230-260°C, and the temperature of temperature control zone 9-10 is 230-260°C.

[0092] The particles prepared in the above Examples 7-11 were tested, and the results are shown in Table 5.

[0093] Table 5 Test results of Examples 7-11

[0094]

[0095] From the test results of Examples 7-11, it can be seen that the V-0 level can be achieved by adding about 4% of the flame retardant. Further increasing the amount can improve the fluidity, but it has a negative impact on the notch impact and transmittance, which can be carefully considered in actual applications.

[0096] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A borosiloxane modified phenolic resin flame retardant, characterized in that: The flame retardant comprises the following components by weight: 1-5 parts of a boron compound; 5-20 parts of oligosiloxane polymer; 5-20 parts of phenolic resin; Wherein, the oligosiloxane polymer is SFR320 of Momentive; or, the oligosiloxane polymer is one or more of polydimethylsiloxane terminated with hydroxyl or alkoxy, polymethylphenylsiloxane terminated with hydroxyl or alkoxy, polymethylethoxysiloxane terminated with hydroxyl or alkoxy, polymethylvinylsiloxane terminated with hydroxyl or alkoxy, polymethylchlorophenylsiloxane terminated with hydroxyl or alkoxy, polymethyltrifluoropropylsiloxane terminated with hydroxyl or alkoxy, polymethylhydroxysiloxane terminated with hydroxyl or alkoxy, polymethylhydrogensiloxane terminated with hydroxyl or alkoxy, polyethylhydrogensiloxane terminated with hydroxyl or alkoxy, or polyhydroxyhydrogensiloxane terminated with hydroxyl or alkoxy; The boron compound includes boric acid, boric acid esters or borate; The preparation of borosiloxane modified phenolic resin flame retardant comprises the following steps: Stirring and mixing the components according to weight to obtain a mixed material; The mixed material is heated, stirred and distilled through a reactor; Then pour it into anhydrous ethanol and dissolve it completely, then pour it into water to precipitate; The precipitated product is filtered and dried, and then crushed and sieved to obtain a borosiloxane-modified phenolic resin flame retardant; The heating process is as follows: the temperature is increased from room temperature to 140-250° C., the heating rate is 10-30° C. / min; the stirring rate is 180-200 rpm; the drying temperature is 60-80° C., and the screen size is 100-400 meshes.

2. A borosiloxane modified phenolic resin flame retardant according to claim 1, characterized in that: The boron compound includes one or more of boric acid, trimethyl borate, triethyl borate, triphenyl borate, potassium tetraphenylborate or sodium tetraphenylborate.

3. The borosiloxane-modified phenolic resin flame retardant according to claim 1, characterized in that: The phenolic resin is in liquid or powder form, wherein the viscosity of the liquid phenolic resin is between 2000-20000 Pa·s at 20°C, and the softening point of the powdered phenolic resin is between 85-115°C.

4. A transparent flame-retardant polycarbonate composite material, characterized in that: The composite material comprises the following components in parts by weight: Polycarbonate resin 70-98 parts; 1-20 parts of the borosiloxane-modified phenolic resin flame retardant according to any one of claims 1 to 3.

5. The transparent flame-retardant polycarbonate composite material according to claim 4, characterized in that: The polycarbonate resin has a melting point of 220-230°C and a density of 1.18-1.22 kg / cm 3 The particle size of the borosiloxane modified phenolic resin flame retardant is 100-400 mesh.

6. The transparent flame-retardant polycarbonate composite material according to claim 4, characterized in that: The composite material also includes the following components by weight: Sulfonate flame retardant 0.01-1 part Compatibilizer 0-0.5 parts; Antioxidant 0.1-1 part; Lubricant 0.1-1 part; The sulfonate flame retardant includes one or a mixture of potassium benzenesulfonylbenzenesulfonate, lithium perfluorobutylsulfonate, sodium perfluorobutylsulfonate, potassium perfluorobutylsulfonate, cesium perfluorobutylsulfonate, potassium perfluorooctanesulfonate, potassium perfluoromethanesulfonate, potassium p-toluenesulfonate or sodium trichlorophenylsulfonate; The compatibilizer includes acrylonitrile-styrene copolymer grafted with maleic anhydride or acrylonitrile-styrene copolymer grafted with glycidyl methacrylate; The antioxidant includes one or a mixture of aromatic amine antioxidants, hindered phenol antioxidants, phosphite antioxidants, thioester antioxidants, aromatic phosphates or pentaerythritol esters; The lubricant includes one or more of silicone oil, white mineral oil, fatty acid amide, barium stearate, magnesium stearate, paraffin, polyethylene wax, ethylene bis stearamide, ethylene-vinyl acetate copolymer, pentaerythritol stearate, ethylene-acrylic acid copolymer or aromatic phosphate.

7. A method for preparing the transparent flame-retardant polycarbonate composite material according to any one of claims 4 to 6, characterized in that: The method comprises the following steps: The components are fully mixed according to weight to obtain a mixed material; The mixed material is placed in a twin-screw extruder, and after melt extrusion and granulation, a flame-retardant transparent polycarbonate composite material is obtained.

8. The method for preparing a transparent flame-retardant polycarbonate composite material according to claim 7, characterized in that: The feeding port temperature of the twin-screw extruder is 50-60°C, including 10 temperature control zones, the temperature of temperature control zone 1-2 is 180-280°C, the temperature of temperature control zone 3-4 is 200-280°C, the temperature of temperature control zone 5-6 is 220-280°C, the temperature of temperature control zone 7-8 is 220-280°C, and the temperature of temperature control zone 9-10 is 240-280°C.

Citation Information

Patent Citations

  • Flame-retardant resin composition

    JP2001031847A

  • Flame retardant polyester resin

    JP2002047398A